STUDI SIMULASI PENGARUH SUDUT DEFLEKTOR PADA SAVONIUS WATER TURBIN DENGAN SUMBU HORIZONTAL TERHADAP POWER GENERATION ALIRAN AIR DALAM PIPA - Ari Prasetyo; Syamsul Hadib; D. Danardono Dwi Prija Tahjana (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2016)
Savonius water turbine is one of the simplest design and low cost production that attracts wide attention. A single stage Savonius water turbine with horizontal axis is applied in a pipe with diameter of 3 inch to give variation in the deflector angle. Deflector is used to focusing the flow so the torque is increased by the blade curvature in the turbine. This simulation uses the SolidWork 2013 software. The aim of this simulation is to obtain the best performance in each deflector angle, then the result is compared with a turbine without deflector. The deflector performance is analyzed by the pressure contour, the torque and the angle of attack. The deflector angle is vary in different angle of 20°, 30°, 40° and 50° with the deflector ratio of 50%. By using debit input of 12,2x10-3 m3/s, the results show that angle deflector of 30° is obtained as the best performance where it produce the pressure contour about 279820,99 Pa, torque of 0,6070 Nm and more stable in angle of attack. Keywords: picohydro, SolidWork, Savonius, deflector, torque